Performance level of sales force automation system in a logistics and distribution company - Cartalla, Kyla Flor Naval; Esguerra, Anthony G.; Cueva, Gene Paul R.; Esguerra, James G. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Logistics and distribution companies turned their interests to using sales force automation (SFA) in their business operations as technology is now a widely used tool that allows fast and efficient operations. A descriptive design was used in this study, and inventory, sales monitoring, and distribution process are the key indicators used to measure the performance of the sales force automation. The results show that the SFA system was perceived as good, with a 4.0 weighted mean. Internet connectivity was the major challenge in the utilization of SFA. Continuous system improvement is recommended to maximize the utilization of the system.